PRONUNCIATION MISTAKE WHICH LEADS TO INCORRECT TRANSCRIPTION BY AUTOMATIC CAPTION GENERATOR - Arif Haryadi; Rahmadsyah Rangkuti (Program Studi Sastra Jepang Fakultas Ilmu Budaya Universitas Bung Hatta, 2022)
This study focuses on the analysis of pronunciation mistakes in the speech which was delivered by the Indonesian President during the 2014 APEC CEO Summit in Beijing, China. This study will provide description on the pronunciation mistakes, the word classes of the words with pronunciation mistakes and its place of articulation. From the result of the analysis, it can be seen that in the Indonesian President’s speech, there were 108 pronunciation mistakes. The main mistakes were made in the part of speech word class of noun 69 times and the place of articulation where the mistakes occurred mostly is in the alveolar area 54 times.